KARAKTERISTIK USAHA KECIL DI INDONESIA Perencanaan Pemasaran Usaha Kecil Rumahan - Sidiq Permono Nugroho (Benefit: Jurnal Manajemen dan Bisnis, 2010)
This paper describes briefly the rules which is closely related to the problems and obstacles in starting a home-based small businesses and  explanations based on theories  from several sources as a reference in running a small business home